Book Review: "Seldom in the Nick of Time": Emil Sîrbulescu's Literatura americană și provocarea etnicității (Papers in Arts and Humanities, 2022)
In 2020, the distinguished professor and scholar from the University of Craiova, Emil Sîrbulescu published the above mentioned book with a view to consolidating the academic research in Romania pertaining to race and ethnicity in the context of American culture and literature. If in the title the readers are threatened with the perspective of a magnum opus—“the challenge of ethnicity”—in the subtitle items seem to be subdued and thus confined to the still complex and complicated space of the African-American novel.Following the introduction, “About cultural diversity,” a first part of the book is dedicated to that particular challenge, as implying the “construction of a multicultural model.” The second part details “the maturing of the African-American novel,” whereas the third provides the readers with a case-study, i.e. Toni Morrison’s works. And last, but not least, the section devoted to conclusions addresses a question that might prove emblematic—whether “the African-American literature still exists.” Our purpose was to highlight both the issues discussed by the author and his solid contribution to the field.
Keywords: ethnicity; race; African-American novel; multiculturalism